Time to completion in the Lagos commercial real estate market: an examination of institutional effects. Issue 2 (3rd April 2018) - Agboola, Alirat Olayinka; Scofield, David
Abstract: This study explores how institutions affect the process of investment and the time it takes to buy and sell commercial property in Lagos, Nigeria. We isolate institutional factors that impact transaction efficiency and provide a snapshot of the process with average transaction times for the largest commercial real estate market in the most populous country in Africa. This study adopts a qualitative approach and relies on information collected from semi-structured interviews with 36 senior level individuals active in the Lagos commercial real estate market. Among our findings, we note the commercial real estate transaction process is divided into seven distinct stages and the average time to complete an acquisition across all stages (all property types) is 306 days. Title registration/perfection stage takes the longest time (around 132 days) and represents a significant risk to investors. We argue this is a consequence of imperfections in the formal institutions of title registration.